Role of Sthanik Chikitsa in Shweta Pradara Associated with Madhumeha (DM Type- II): A Case Study (International Journal of Ayurveda and Pharma Research, 2023)
Shweta Pradara or excessive vaginal discharge is one of the commonest complaints among women of reproductive age group. An increase in the normal vaginal secretion develops physiologically at puberty, at ovulation, premenstrual phase and during pregnancy. Excessive discharge causes irritation and itching in the genetalia. Ayurveda explained this condition as Shweta Pradara. Shweta Pradara is a symptom which is present in most of the diseases or present as a complication. Shweta Pradara is not a disease it produces as a symptom, hence etiopathogenesis of principal disease and Shweta Pradara would be same. It is a Kaphaja disorder at the place of Apana Vayu. A 47 years old female patient suffering from intermittent Yonigata Shwet Strava since two years with aggravation of symptoms from one week presented to Prasuti Tantra Evam Stree Roga OPD. Yonigat Shwet Strava was associated with Yoni Kandu, Katishool, Yoni Daha. On enquiry, it was found that she was the known case of Type II Diabetes Mellitus since 10 years. She was taking medication for the same but her blood sugar levels were uncontrolled in spite of taking medication as per her recent investigations. In this case Shwet Pradar was the Updrava of Madhumeh, thus line of management was planned to control her sugar level by supplementing Ayurvedic drugs along with allopathic medicine for DM II (Madhumeh) and treated her with Yoniprakshalan with Triphala Kwath followed by Cutis ointment tamponing per vaginum for 14 days. She had followed the schedule of Yoni Prakshalana, oral medicines and Pathya-Apathya properly. It was observed that, symptoms were started to reduce gradually which has been depicted by documentation of investigations and local examination in this case study.